Gel Formulation from a Combination of Sidaguri Leaf Extract (Sida rhombofolia L.) and Chinese Petai Leaves (Leucaena leucocephala L) as Inhibitors of Acne-causing Bacteria (Propionibacterium acne and Staphylococcus aureus) - Andriana, Andriana; Chaidir, Chaidir; Rahmat, Deni (Journal of Natural Product for Degenerative Diseases, 2023)
Acne vulgaris, a chronic inflammatory disease of the pilosebaceous unit, is the most common skin condition. Propionibacterium acnes and Staphylococcus aureus are two bacteria that can cause infections. Chinese Petai leaves are known to inhibit acne growth. Sidaguri leaves are also thought to have antibacterial activity. The aims of this study were to determine the effect of the combination of the two extracts on inhibiting the growth of acne-causing bacteria, also to test the gel formula to meet physical and chemical parameters as well as stability to temperature and storage, as well as to test acute dermal. irritation to rabbits. Each extract with a concentration of 0.19%; 0.39%; 0.78%; 1.56%; 3.125%; 6.25%; 12.5%; 25%; 50% were incubated and then the inhibition zone was measured, then the minimum inhibition zone concentration of the two extracts was determined to determine the lowest concentration of the extract that still provided antibacterial activity against the tested bacteria using the well-diffusion method. The extract combination is formulated in a gel preparation with Carbopol 940, Propylene glycol, Phenoxyethanol, TEA, and Aquadest as excipients. Test the antibacterial activity of gel preparations using the well method with positive control clindamycin gel. Then evaluation of the formula includes evaluation of physics, chemistry, and microbiology. The results showed that the combination gel had activity against P. acne and Staphylococcus aureus at a concentration of 3.12% : 1.56%. The combined gel preparation of the two extracts also has a synergistic effect in inhibiting acne bacteria. The formula is resistant to temperature and storage, and it can satisfy chemical and physical parameters.